2014
DOI: 10.1111/jcmm.12245
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of hydrogen‐rich saline against radiation‐induced immune dysfunction

Abstract: Recent studies showed that hydrogen can be used as an effective radioprotective agent through scavenging free radicals. This study was undertaken to evaluate the radioprotective effects of hydrogen on immune system in mice. H2 was dissolved in physiological saline using an apparatus produced by our department. Spleen index and histological analysis were used to evaluate the splenic structural damage. Spleen superoxide dismutase, GSH, MDA were measured to appraise the antioxidant capacity and a DCF assay for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 23 publications
0
31
0
1
Order By: Relevance
“…The immune system is one of the most important defense mechanisms against IR ( Zhao et al, 2014 ). The damage degree of normal tissue in radiation is dependent on the dose, tissue sensitivity, repair capacity, and prevailing endogenous antioxidant defenses.…”
Section: Discussionmentioning
confidence: 99%
“…The immune system is one of the most important defense mechanisms against IR ( Zhao et al, 2014 ). The damage degree of normal tissue in radiation is dependent on the dose, tissue sensitivity, repair capacity, and prevailing endogenous antioxidant defenses.…”
Section: Discussionmentioning
confidence: 99%
“…Radiation-induced Th1/Th2 imbalance also accounts for immunosuppression in irradiated animals and human [32]. Even after a long time, when the structure of immune organs is reconstructed, immunity remains suppressed [7].…”
mentioning
confidence: 99%
“…It has also been reported that use of H 2 -enriched saline in mice protects immune system function and spleen inflammation induced by radiation. Biomarkers of oxidative stress, inflammation, apoptosis and immune response capacity were all improved after hydrogen-enriched saline administration [295].…”
Section: Hydrogen In Inflammatory Diseasesmentioning
confidence: 93%